Mechanical properties comparison of phenylsilsesquioxane–methylsilsesquioxane hybrid ﬁlms by indentation - Ainuddin, Ainun Rahmahwati; Hakiri, Norio; Muto, Hiroyuki; Sakai, Mototsugu; Matsuda, Atsunori (The Ceramic Society of Japan, 2011)
Solgel derived phenylsilsesquioxane (PhSiO3/2)methylsilsesquioxane (MeSiO3/2) ﬁlms were prepared on soda-lime-silicate (SLS) glass substrates by dropping and spreading method. The mechanical properties of the pure MeSiO3/2 and 20PhSiO3/2· 80MeSiO3/2 (inmol%) ﬁlms were measured as a function of heat treatment times and temperatures using a nanoindentation test with a Berkovich indenter. The relative residual depth (²r)ofﬁlms decreased and the ﬁlm hardness (HM)signiﬁcantly increased with increasing heat treatment times and temperatures. The mechanical properties of the ﬁlms well reﬂect the changes in the chemical structures and the evolution of siloxane networks with the heat treatment.